Charge Injection: Asymmetric Split‐Gate Ambipolar Transistor and Its Circuit Application to Complementary Inverter (Adv. Mater. Technol. 4/2016). Issue 4 (July 2016) - Yoo, Hocheon; Smits, Edsger C. P.; van Breemen, Albert J. J. M.; van der Steen, Jan‐Laurens P. J.; Torricelli, Fabrizio; Ghittorelli, Matteo; Lee, Jiyoul; Gelinck, Gerwin H.; Kim, Jae‐Joon
Abstract : In article number 1600044, Jiyoul Lee, Gerwin H. Gelinck, Jae‐Joon Kim, and co‐workers present a novel ambipolar split‐gate thin‐film transistor (TFT). Depending on the bias voltage at the side‐gate, an ambipolar TFT can operate as an either p‐type or n‐type device selectively. A complementary inverter based on ambipolar split‐gate TFTs is demonstrated, which shows the higher noise margin and DC‐gain.